Naval science 2 maritime history, leadership, and nautical sciences for the NJROTC student - Hobbs, Richard R (Naval Institute Press, 2014)
Naval Science 2, 3rd Edition is the new edition of a textbook that has long been a staple work for the NJROTC program. It provides a survey of early maritime history as well as the history of the U.S. Navy. In addition, this textbook covers the key leadership precepts and nautical sciences required by second-year students in the Navy high school NJROTC program. Subjects covered include maritime geography, oceanography, meteorology, astronomy, and physical science, including timely topics such as global warming, green energy, and computer science. The highly illustrated text provides the fundamental background necessary for follow-on studies in all these areas at either the senior high school or college level.